Identification of sex-specific transcripts of the Anopheles gambiae doublesex gene - Scali, Christina (2005)
The understanding of the molecular mechanisms of sex differentiation in the mosquito Anopheles gambiae could identify important candidate genes for inducing selective male sterility in transgenic lines or for sex-controlled expression of lethal genes. In many insects doublesex (dsx) is the double-switch gene at the bottom of the somatic sex-determination cascade that determines the differentiation of sexually dimorphic traits. We report here on the identification of the dsx homologue in A. gambiae, and on the characterization of its sex-specific transcripts. Agdsx consists of 7 exons distributed over an 85 kb region on chromosome 2R, which are sex-specifically spliced to produce the female and male AgdsxF and AgdsxM transcripts. AgdsxF contains a 795 bp ORF, coding for a protein of 265 amino acids, while AgdsxM comprises a much longer (1866 bp) ORF, coding for a 622 aa protein. Differences in the exon/intron organization suggest that Agdsx sex-specific splicing results from a different mechanism from Drosophila melanogaster dsx. These findings represent an important step towards the understanding of sex differentiation in Anopheles and will facilitate the use of gene transfer technologies to manipulate sex ratios for vector control programs based on the Sterile Insect Technique.